(untitled) (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: this research aims to know the implementation of the policy of retributionMarket Bersehati Subdistrict Detention Manado city. This study uses qualitative methods with selected informants consisted of Director of PD. The market town of Manado, head of Retribution PD. Manado City Market, Bersehati Market, Officer Coordinator/Billers Levy Bersehati Market, and Traders in the market Bersehati. Data collection techniques used are interviews, observation and documentation. Qualitative datawere analyzed with descriptive narrative supported by primary and secondary data.The results showed that the implementation of policies related Market levy Bersehati sub-district of Manado City Detention has shown a fairly good results, in terms ofattitude, and the compliance officer in carrying out the policy. This can be seen on the Apparatus involved in the implementation of the Bersehati sub-district of Markets ballot levy arbitrary arrest city that transparency in carrying out the tasks and always refers to the existing regulations. In addition the adequacy of manpower is already implementing a policy that is good with officers and employees of the PD marketManado city that exists in the market Bersehati. Similarly, the decisions taken in case of problems or constraints in implementation is always good for the common goodparty PD. Manado City Market or user community market. However for the benefit of employees and response against complaint merchants still showed a less good results. Similarly, the strategies used are all just communication and sosialisai without any action even though the degree of change that’s been good to be achieved, namely repair and upgrading of infrastructure and quality of service. So consequently the traders became feel aggrieved. Keywords: Implementation Of Policy, Market Levy